2013
DOI: 10.1108/ijqrm-jun-2011-0076
|View full text |Cite
|
Sign up to set email alerts
|

Detection of shift in process mean withchart for autocorrelated data

Abstract: Purpose -The purpose of this paper is to study the performance of the X-bar chart on the basis of average run lengths (ARLs) for the positively correlated data. The ARLs at various sets of parameters of the X-bar chart are computed by simulation. The performance of the chart at the various shifts in the process mean is compared with the X-bar chart suggested by Zang and residual chart proposed by Zang. The optimal schemes suggested in this paper are also compared with variable parameters (VP) chart and double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The idea is to establish an upper warning limit below the upper control limit (UCL), and adjust the sample size or sampling interval when sample results fall between the warning and control limits. Hashemian et al (2016) Variable data Attribute data Static control charts Duncan (1956Duncan ( , 1971, Cowden (1957), Gibra (1967Gibra ( , 1971, Goel et al (1968), Taylor (1968), Knappenberger and Grandage (1969), Baker (1971), Saniga (1977Saniga ( , 1979, Saniga and Montgomery (1981), Lorenzen and Vance (1986), Costa (1993Costa ( , 1998Costa ( , 1999, Singh and Prajapati (2013), Oprime andMendes (2017) Ladany (1973), Chiu (1975Chiu ( , 1976, Ladany and Alperovitch (1975), Montgomery et al (1975), Alperovitch and Friedman (1976), Sculli and Woo (1976), Duncan (1978), Gibra (1978), Saniga and Montgomery (1981), von Collani (1989), Darestani et al (2014) Adaptive control charts Reynolds et al (1988), Runger and Pignatiello (1991), Prabhu et al (1993Prabhu et al ( , 1994, Park and Reynolds (1994), , , Bai and Lee (1998), Zimmer et al (1998),…”
Section: Adaptive Control Chartsmentioning
confidence: 99%
“…The idea is to establish an upper warning limit below the upper control limit (UCL), and adjust the sample size or sampling interval when sample results fall between the warning and control limits. Hashemian et al (2016) Variable data Attribute data Static control charts Duncan (1956Duncan ( , 1971, Cowden (1957), Gibra (1967Gibra ( , 1971, Goel et al (1968), Taylor (1968), Knappenberger and Grandage (1969), Baker (1971), Saniga (1977Saniga ( , 1979, Saniga and Montgomery (1981), Lorenzen and Vance (1986), Costa (1993Costa ( , 1998Costa ( , 1999, Singh and Prajapati (2013), Oprime andMendes (2017) Ladany (1973), Chiu (1975Chiu ( , 1976, Ladany and Alperovitch (1975), Montgomery et al (1975), Alperovitch and Friedman (1976), Sculli and Woo (1976), Duncan (1978), Gibra (1978), Saniga and Montgomery (1981), von Collani (1989), Darestani et al (2014) Adaptive control charts Reynolds et al (1988), Runger and Pignatiello (1991), Prabhu et al (1993Prabhu et al ( , 1994, Park and Reynolds (1994), , , Bai and Lee (1998), Zimmer et al (1998),…”
Section: Adaptive Control Chartsmentioning
confidence: 99%
“…The comparison of performance on the basis of average run lengths (ARLs) of the modified X chart with the Shewhart X chart for correlated data has already been given in Singh and Prajapati [5].…”
Section: -P2mentioning
confidence: 99%
“…They observed that by implementing same, the cost of quality reduces significantly in the chosen industry. Singh and Prajapati [5] suggested the optimal schemes of X chart and compared with VP X chart and DS X chart, suggested by Costa and Machado [18]. Mitra and Clark [23] focused on determining changes in process variability of multivariate processes.…”
Section: -P2mentioning
confidence: 99%
See 1 more Smart Citation